Mozart's 'La clemenza di Tito': A Reappraisal - Tessing Schneider, Magnus; Tatlow, Ruth (Stockholm Studies in Culture and Aesthetics, 2018)
"In the two centuries since Mozart's La clemenza di Tito was first performed, and the almost three centuries since Metastasio created the libretto, many rumours, myths and prejudiced opinions have gathered around the work, creating a narrative that Mozart, Mazzolà and their contemporaries would scarcely recognise. The essays in this book contribute ideas, facts and images that will draw the twenty-first-century reader closer to the events of Central Europe in the late eighteenth century, and these new facts and ideas will help peel off some of the transmitted accretions that may hinder a modern listener from enjoying and understanding the opera in all its fullness. In this sense the essays present the reappraisal promised in the title. The book is a product of the Performing Premodernity research project, funded by the Swedish Foundation for Humanities and Social Sciences and based at the department of theatre studies of Stockholm University. Envisioned and edited by Magnus Tessing Schneider and Ruth Tatlow, the five essays by internationally renowned Mozart scholars are preceded by a chronology and a selection of original documents presented in new and revised parallel translations."